Effects of Intermittent Fasting in Human Compared to a Non-intervention Diet and Caloric Restriction: A Meta-Analysis of Randomized Controlled Trials - Gu, Lihu; Fu, Rongrong; Hong, Jiaze; Ni, Haixiang; Yu, Kepin; Lou, Haiying (Frontiers in Nutrition, 2022)
Background: The popularity of applying intermittent fasting (IF) has increased as more and more people are trying to avoid or alleviate obesity and metabolic disease. This study aimed to systematically explore the effects of various IF in humans. Methods: The randomized controlled trials (RCTs) related to IF versus non-intervention diet or caloric restriction (CR) were retrieved in PubMed, Web of Science, the Cochrane Library database, and Embase. Extraction outcomes included, but not limited to, weight, body mass index (BMI), waist circumference (WC), fasting glucose, and triglyceride (TG). Results: This study included 43 randomized controlled trials with 2483 participants. The intervention time was at least one month, and the median intervention time was 3 months. Contrasting results between IF and non-intervention diet showed that, participants had lower weight (weighted mean difference (WMD)=1.10, 95%CI: 0.09-2.12, p=0.03) and BMI after IF (WMD=0.38, 95%CI: 0.08-0.68, p=0.01). The WC of participants after IF decreased significantly compared with the non-intervention diet (WMD=1.02, 95%CI: 0.06-1.99, p=0.04). IF regulated fat mass (FM) more effectively than non-intervention diet (WMD=0.74, 95%CI: 0.17-1.31, p=0.01). The fat-free mass of people after IF was higher (WMD=-0.73, 95%CI: (-1.45)-(-0.02), p=0.05). There was no difference in fasting blood glucose concentrations between participants in the after IF and non-intervention diet groups. The results of insulin concentrations and HOMA-IR, though, indicated that IF was significantly more beneficial than non-intervention diet (standard mean difference (SMD)=-0.21, 95%CI: 0.02-0.40, p=0.03, and WMD=0.35, 95%CI: 0.04-0.65, p=0.03, respectively). Cholesterol and TG concentrations in participants after IF were also lower than that after a non-intervention diet (SMD=0.22, 95%CI: 0.09-0.35, p=0.001, and SMD=0.13, 95%CI: 0.00-0.26, p=0.05, respectively). IF outcomes did not differ from CR except for reduced WC. Conclusion: IF was more beneficial in reducing body weight, WC, and FM without affecting lean mass compared to non-intervention diet. IF also effectively improved insulin resistance and blood lipid conditions compared with non-intervention diets. However, IF showed little benefit over CR.